Synthesis of monodisperse chitosan nanoparticles. (October 2018) - Sullivan, David Joseph; Cruz-Romero, Malco; Collins, Timothy; Cummins, Enda; Kerry, Joseph P.; Morris, Michael A.
Abstract: The objectives of this study were to evaluate the effects of the initial concentrations of chitosan (CS) and sodium tripolyphosphate (TPP), the CS:TPP mass ratio, the CS molecular weight (MW) and pH on the synthesis of CS nanoparticles (CS NPs). The particle size of the synthesised CS NPs was significantly affected ( P  < 0.05) by these parameters. Self-assembled monodisperse CS NPs with a particle size of 90 nm and zeta potential of 30.15 mV were successfully synthesised using solutions of 0.1% low MW CS at pH 4.6 and 3:1 (CS:TPP) mass ratio. When higher concentrations of CS were used, application of external forces (tip sonication or Ultra-Turrax™) was necessary to induce monodispersity and significantly ( P  < 0.05) reduce the particle size; however, the particle sizes were >300 nm. While both native CS and CS NPs showed antimicrobial activity, no significant antimicrobial enhancement was observed for the NP form. The findings of this study have shown that monodisperse CS NPs can be obtained using a combination of bottom-up and top-down techniques and the unique physiochemical properties of these nanomaterials have the potential for applications in developing of antimicrobial active packaging materials. Graphical abstract: Image 1 Highlights: CS NPs were prepared by ionic gelation using different initial concentrations of CS and TPP, CS:TPP mass ratios, CS MW and pH. Monodisperse CS NPs with a 90 nm diameter & 30 mV zeta potential were made using 0.1% L. MW CS at pH 4.6 in a 3:1 mass ratio. Higher concentrations of CS NPs required tip sonication to induce monodispersity; however, particle size was >300 nm. The unique physiochemical properties of these nanoparticles show potential for applications in antimicrobial active packaging.